Complex estimation of a state of health of first-graders in the process of adaptation to training in educational institutions new type - L. M. Zakirova; T. A. Nagayeva; I. I. Balasheva; D. A. Ponomaryova; A. A. Ilinich; A. A. Semyonova; T. V. Matkovskaya (Бюллетень сибирской медицины, 2012)
The state of health, vegetative homeostasis and parameters of local immunity 104 first-graders at the age of 6—8 years in adaptation to training in educational institutions of the general type and with the raised academic load is studied. It is shown that the current of adaptable process of the first-graders trained in educational institutions of new type is interfaced to growth of a chronic pathology, infringement of a vegetative homeostasis and a condition of local immunity of mucous membranes (maintenance increase sekretori immunoglobulin A, activity decrease kaspazy-3 asaliva), testifying to decrease in nonspecific resistance of an organism of children.